Trends in snow water equivalent in Rocky Mountain National Park and the northern Front Range of Colorado, USA - Patterson, Glenn G., author; Fassnacht, Steven R., advisor; Laituri, Melinda J., committee member; Sanford, William E., committee member; Pritchett, James, committee member (Colorado State University. Libraries, 2016)
The seasonal snowpack in Rocky Mountain National Park and the northern Front Range of Colorado, USA, within 50 km of the park, is undergoing changes that will pose challenges for water providers, natural resource managers, and winter recreation enthusiasts. Assessing long-term temporal trends in measures of the seasonal snowpack, and in the climatic factors that influence its annual accumulation and ablation, helps to characterize those challenges. In particular, evaluating the patterns of variation in those trends over different parts of the snow season provides new understanding as to their causes. This also helps to determine specific ramifications of the trends. In addition, placing the current 35-year trends in the longer context of longer-term observational records, and paleoclimate tree-ring reconstructions, provides useful comparisons of current and past trends. Finally, projections of future trends provided by linked climate and hydrologic models offer a sense of how these trends are likely to affect the snowpack of the future. Some factors such as the high elevation of the study area help to preserve conditions favorable to development of the seasonal snowpack, and hence to limit trends toward greater warming-induced melt and less precipitation falling as snow. Nevertheless, traditional snowpack measures such as April 1 snow water equivalent (SWE) show consistent declining trends over the 35-year period of record for automated snow monitoring stations in the study area. The trends are not uniform throughout the snow season, but vary significantly by month. As a result, November and March have warming and drying trends that delay the beginning of the winter snow season and reduce the traditional accumulation that formerly characterized the early spring. In contrast, the core winter months of December, January, and February have cooling and wetting trends that have been enhancing SWE during the heart of the winter. Mid-April to early May is another period during which cooling and wetting trends have been enhancing SWE, although these months also show more variability. This oscillating pattern helps to explain why there has not been a pervasive shift to earlier and lower annual peak SWE in the study area. Paleo SWE reconstructions based on tree-ring chronologies show that at least some of the recent 35-year trends in observed SWE described in this study have comparable precedents during the preceding five centuries, but we do not yet know how long the recent trends will continue. Linked climate and hydrologic models project that the observed trends are likely to continue, and that by 2050 measures such as April 1 SWE in the study area are likely to decrease by 25 percent.